TESTING OF ACCEPTANCE AND NUTRITIONAL VALUE OF KATUK LEAF FLOUR FLOUR CHIPS AND WHITE SWEET FLOUR AS ADDITIONAL FOOD FOR BREASTFEEDING MOTHERS - Apriyanti, Rita; Afida, Anna Martiana; Candra Kusuma Negara (Jurnal EduHealth, 2022)
Leaf katuk and sweet potato white potential are sources of substance nutrition because they contain neither macro nor micro substance nutrition. One _ form utilizes leaf katuk and sweet potato white; with the process, it becomes flour and is used to manufacture chips. Study this experiment with two treatments: chips with addition flour leaf Katuk 20%, sweet potato flour 10% white, flour leaf katuk 15%, and sweet potato flour white 15%. Organoleptic test chips were conducted by 30 panelists conducted on UCB students with Analysis content calcium, protein, fat in chips flour leaf katuk and sweet potato flour white carried out at the Laboratory of the Research and Standardization Agency Medan Industry. Test results laboratory show that content nutrition calcium, protein, and fat produced in treatment A1 ( flour leaf Katuk 20% and Sweet Potato Flour white 10%) each with 487.0 mg /kg, 5.22% protein, 28.8% crude fat. While in treatment A2 ( flour leaf katuk 15% and sweet potato flour white 15%) each of 338.9 mg/kg, 5.34% protein, 31.8% crude fat. Test to organoleptic data used with Wilcoxon Signed Rank method. Based on organoleptic test on taste, aroma, color, and texture, most favorite chips panelists are chips with addition flour leaf katuk 15% and sweet potato flour white 15% (A2) while on the addition of flour leaf Katuk 20% and sweet potato flour white 10% (A1) only liked panelists from aspect color and texture. Recommended to the community to make chips flour leaf katuk and sweet potato flour white as food Intermezzo because contain Calcium, protein, fat needed body specifically mother breastfeeding and valuable for health. Need Diversification is also carried out food besides leaf katuk and sweet potato white as rich food _ substance nutrition.